La presse sportive écrite à la limite de la langue écrite et de la langue parlée: L’apposition dans la presse sportive écrite - Valentová, Eva (Verbum – Analecta Neolatina, 2006)
As the corpus studies of the paper reveal, apposition, as we define it, is less frequent in the written sport press, though it is typical of written discourse in general. The rare samples found accompany proper names quasi-exclusively: this construction is very commonly found in the appositive structures of spoken language. This phenomenon could be explained by the fact that the style of the written sport press approximates that of oral language. However, apposition gradually appears in the sports press, too (particulary, in the headlines of articles) as a subtle but powerful lexico-syntactic tool.